Medical complications during interhospital transfer for thrombectomy in patients with acute ischemic stroke - Mirkov, Damjan; Jenetzky, Ekkehart; Thieme, Andrea; Qabalan, Adeeb; Gumbinger, Christoph; Wick, Wolfgang; Ringleb, Peter A.; Rizos, Timolaos (European stroke journal, 2024)
Introduction: Patients with acute ischemic stroke (AIS) and large-vessel occlusion are frequently transferred by emergency physicians (EPs) from primary to comprehensive stroke centers (CSC) for thrombectomy, particular when thrombolysed. Data on complications during such transfers are highly limited. - Patients and methods: Consecutive AIS patients transferred between 01/2015 and 10/2021 to our CSC were included. Associations of major (MACO) and minor (MICO) complications with clinical and imaging data were assessed. - Results: In total, 985 patients were included in the analysis (58.5% thrombolysed). MACO developed in 1.6%, MICO in 14.6%. Compared to patients without complications (NOCO), patients with MACO did not differ in terms of demographics, cerebrovascular risk factors, or site of vessel occlusion. They had more severe strokes (p = 0.026), neurological worsening was more severe (p = 0.008), and transport duration was longer (p = 0.050) but geographical distances did not differ. Thrombolysed patients had any complication more often than patients without thrombolysis (20.3% vs 10.5%; p < 0.001); however, this finding was driven by patients with MICO (p < 0.001) only (MACO: p = 0.804). No associations were observed between stroke severity and complications in either thrombolysed or nonthrombolysed patients. Neurological deterioration during transfer was observed in 21.2%, but multivariate analysis revealed no association with thrombolysis (OR 0.962; 95%CI 0.670-1.380, p = 0.832). Asymptomatic intracerebral hemorrhage was present in 1.1%, symptomatic in 0.1%. - Discussion and conclusion: In this large cohort, no patient-specific factor increasing the risk of complications during interhospital transfer was identified. Specifically, our results do not indicate that thrombolysis increases MACO. Hence, interhospital transfer without EPs appears reasonable in most patients.